Physico-chemical and harvest time alterations in pineapple fruits Smooth Cayenne caused by paclobutrazol - Antunes,Andréa Maria (2008)
The aim of this work was to assess the effect of an inhibitor acting in the floral differentiation on the physico-chemical characteristics of pineapple fruits and on the effect in the harvest time. Paclobutrazol was used at concentrations of 100, 150, and 200 mg L-1, applied 2, 3 or 4 times in Smooth Cayenne pineapple plants. The treatment did not influence the chemical characteristics of the fruits, and even having some physical alterations, they were within the quality standard for the commercialization. The harvest time was amplified in all the treatments comparing to the control. However, 150 mg L-1 applied twice promoted the best result when analyzing together the harvest time and the fruit fresh matter.